Inflammatory Bowel Disease and Pregnancy: Is It a Marker for Adverse Outcomes? - Costa, Rita Vicente; Simões, Carolina; Correia, Luís; Pinto, Luísa (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To assess obstetric/puerperal/neonatal outcomes in an inflammatory bowel disease (IBD) population and to analyze disease characteristics that may be associated to adverse outcomes.Methods Retrospective descriptive analysis including 47 pregnant women with IBD (28 with Crohn's disease – CD and 19 with ulcerative colitis – UC) who delivered between March 2012 and July 2018 in a tertiary hospital. We reviewed clinical records to extract demographic information, previous medical history, disease subtype, activity, severity, treatment, and obstetric, puerperal, and neonatal outcome measures.Results Obstetric and neonatal complications (composite outcomes) occurred in 55.3% and 14.6% of the IBD population, respectively, and were more frequent in UC patients. Preterm birth (PTB), preeclampsia, anemia, low birth weight (LBW), and neonatal death were also more frequent in UC patients. The rate of postpartum hemorrhage (PPH) was 14.9%, and it was higher in CD patients. Women with active IBD had more obstetric/neonatal adverse outcomes (fetal growth restriction and LBW in particular) and cesarean sections. Patients with medicated IBD had less obstetric/neonatal complications (PTB and LBW in specific) and cesarean sections but more PPH.Conclusion Women with IBD may have an increased risk of obstetric/puerperal/neonatal adverse outcomes. Ulcerative colitis patients had more obstetric and neonatal complications, whereas PPH was more frequent if CD patients. Other disease characteristics were considered, which allowed a better understanding of their possible influence. Although more research is needed, this work reinforces the importance of adequate surveillance to allow prompt recognition and treatment of complications.
Keywords: inflammatory bowel diseases; pregnancy; retrospective studies